PENGARUH PENUTUPAN PINTU PERLINTASAN KERETA API TERHADAP TUNDAAN DAN PANJANG ANTRIAN KENDARAAN PADA JALAN BUNG TOMO SURABAY - Djaelani, Mohamad (EXTRAPOLASI: Jurnal Teknik Sipil, 2014)
Congestion and delays in urban areas is a critical problem faced by many large cities, especially in the region of East Java, especially in Surabaya has resulted in an increased mobility of people and goods where the rate of vehicle ownership and traffic congestion often occurs highway traffic, the purpose of this study is to find a model suitable to describe the relationship between the length of delay due to the closure of railroad crossings and traffic volume, the degree of saturation of traffic conditions, and queue length variation due to the closure of the old railroad crossings and traffic volume. To obtain sufficient data variation, the data collection for 4 days that is Monday, Tuesday, Wednesday and Thursday with a time of observation for approximately 11 hours starting from 06:00 pm until 18:00 pm. In addition to the data variable traffic volume, long crossings closures, delays and queue length measurements done anyway EMP (passenger car equivalent)During 4 (four) days of observation group the data obtained at the same time closing the crossings with a total sample of 203 groups of data. Old variable closing crossings are used to determine how much influence the closure of crossings to the long delay (delay) and the length of the queue (queue). Variations long closure while crossing tabulated in the appendix to the maximum value, minimum and average length of the closure of crossings is the maximum value of 183.75 seconds, the minimum value of 26.28 seconds, 71.68 seconds average.Â  Observation of traffic volume made every fifteen-min during the observation period. During the four days of observation obtained maximum value of traffic volume 2,221.60 smp / hour / lane, the minimum value 964.00 smp / hour / lane, average 1,620.47 smp / hour / laneÂ Observations stopped time delay is performed to determine how the average delay experienced by the vehicle during the crossing closed doors. During the 4 days of observation obtained maximum value of stopped time delay 6,832.60 sec vehicle / lane minimum value 81.33 sec vehicle/lane, average 1,197.99 sec vehicle / laneKeyword : Delay Time